Racial differences of colorectal cancer in a single institution in Northeast Louisiana primarily serving the underserved population (Health Renaissance, 2012)
Background: Colorectal cancer (CRC) screening has helped decrease the incidence of CRC in the last two decades. Still African Americans share a higher burden of CRC disease in the United States in comparison to Caucasians. Objective: To study racial differences of colorectal cancer in low income patients. Methods: Retrospective chart review of all admitted patients with a diagnosis of CRC was done by the lead author over a period of eight months. Results: This study, drawn from a poor, diverse population of Louisiana residents suggests socioeconomic factors may explain observed differences in CRC rates between African Americans and Caucasians. Conclusion: Large scale surveillance studies that address social determinants of CRC are needed to further explore this association. DOI: http://dx.doi.org/10.3126/hren.v10i1.5998 HREN 2012; 10(1): 5-7